GlcNAc-1,6-anhydro-MurNAc moiety affords unusual glycosyl acceptor that terminates peptidoglycan elongation - Zhang, Xiao-Lin (2024)
Peptidoglycan (PG), an essential exoskeletal polymer in bacteria, is a well-known antibiotic target. PG polymerization requires the action of bacterial transglycosylases (TGases), which couple the incoming glycosyl acceptor to the donor. Interfering with the TGase activity can interrupt the PG assembly. Existing TGase inhibitors like moenomycin and Lipid II analogues always occupy the TGase active sites; other strategies to interfere with proper PG elongation have not been widely exploited. Inspired by the natural 1,6-anhydro-MurNAc termini that mark the ends of PG strands in bacteria, we hypothesized that the incorporation of an anhydromuramyl-containing glycosyl acceptor by TGase into the growing PG may effectively inhibit PG elongation. To explore this possibility, we synthesized 4-O-(N-acetyl-β-d-glucosaminyl)-1,6-anhydro-N-acetyl-β-d-muramyl-l-Ala-γ-d-Glu-l-Lys-d-Ala-d-Ala, 1, within 15 steps, and demonstrated that this anhydromuropeptide and its analogue lacking the peptide, 1-deAA, were both utilized by bacterial TGase as noncanonical anhydro glycosyl acceptors in vitro. The incorporation of an anhydromuramyl moiety into PG strands by TGases afforded efficient termination of glycan chain extension. Moreover, the preliminary in vitro studies of 1-deAA against Staphylococcus aureus showed that 1-deAA served as a reasonable antimicrobial adjunct of vancomycin. These insights imply the potential application of such anhydromuropeptides as novel classes of PG-terminating inhibitors, pointing toward novel strategies in antibacterial agent development.